What Drives Academic Engagement in Digital Higher Education? The Roles of Digital Competence, Academic Self-Efficacy, and Emotional Intelligence - Rudy Pratama; Niko Sudibjo (Universitas Katolik Soegijapranata, 2026)
This study investigates the relationships between digital competence, academic self-efficacy, emotional intelligence, and academic engagement among undergraduate students in Jakarta. The study hypothesizes that digital competence, academic self-efficacy, and emotional intelligence are positively associated with academic engagement simultaneously. A quantitative non-experimental design was employed using a non-probability convenience sampling technique, and data were collected through questionnaires administered to 211 participants. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings support the proposed hypotheses. Digital competence demonstrated the strongest positive effect on academic engagement (β = 0.459), followed by academic self-efficacy (β = 0.406) and emotional intelligence (β = 0.367). Collectively, these variables explained 71.8% of the variance in academic engagement (R² = 0.718). These findings suggest that developing students’ personal capacities is essential for sustaining academic persistence within increasingly digitalized higher education environments.